(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
The construction of the Al-Faw port project and the dry canal project, and the completion of the transportation infrastructure for these two projects, are among the main pillars of supporting the Iraqi economy through the expansion of national import and export programs in the long term. This will lead to encouraging and attracting transit trade through Iraq by shifting the maritime transport traffic from northern, central, and southern Europe to Iraq. The port of Al-Faw and the Dry Canal lead to the development of the southern region of Iraq, thus absorbing unemployment, and developing the infrastructure for the transport sector. Therefore, the research concluded the importance of developing, building, and modernizing the Iraqi railway network and the highway network, and the need for a kind of balance between the AlFaw port project, which has capabilities and specifications that meet the needs of modern shipping, with the modern road and railway network project, as these two projects are considered a prerequisite for the success of the project. dry channel.